Home Pharmacy Care Meningkatkan Kepuasan Pelayanan Kefarmasian - Rizki Rahmah Fauzia; Ahmad Azrul Dzuniarto; Cut Diva Rachma Alya Putri; Fitri Nurul Ramadhani (LPPM ITEKES Mahardika, 2026)
Background: Home Pharmacy Care (HPC), a home visit service by pharmacists to provide education, counseling, and monitoring of safe, effective, and rational drug use, has not yet become part of the routine service program at Pharmacies. Objective: This study aims to determine the effect of Home Pharmacy Care on the level of satisfaction with pharmaceutical services at Pharmacy S in Sukamandi Jaya, Subang Regency. Method: The research method used is descriptive quantitative with a pre-experimental design approach. The research sample consisted of 30 respondents who had a history of cholesterol and met the inclusion criteria. Data were collected using a questionnaire based on five dimensions of SERVQUAL and leaflet as a medium used for HPC. Data analysis was carried out using the McNemar test. Results: The test results showed a significant effect of Home Pharmacy Care on increasing satisfaction with pharmaceutical services at Syiara Pharmacy (p < 0.05). Conclusion: Home Pharmacy Care has a positive effect on increasing patient satisfaction with pharmaceutical services, so it can be used as a routine strategy in pharmacy services, especially for strengthening the role of pharmacists as drug consultants and part of the primary health team in the community.